Management of leaf eating caterpillars through intercropping with Suva, Anethum graveolens in soybean: Management of leaf eating caterpillars through intercropping with Suva, Anethum graveolens in soybean - R CHANNAKESHAVA; G SOMANAGOUDA; SHALINI N HUILGOL; G K NAIDU; HARSHIYA BANU (Journal of Oilseeds Research, 2023)
Defoliators are common insect pests of soybean and often cause economic losses. Insecticides are the first option that farmers choose to minimize the damage caused by the defoliators, and the result is not only the emergence of resistance to insecticides in the pests but also environmental pollution. A field experiment carried out at the UAS, Dharwad, India, during Kharif 2021 tested different combinations of Soybean+suva intercrop for their ability to reduce the damage caused by defoliators to soybean leaves and the effect on grain yield of soybean. Among these, Soybean + Suva (3 soybean: 2 suva: 3 soybean rows combination) was effective in reducing larval population.